L’investissement des blogueurs littéraires dans la prescription et la reconnaissance: compétences et ambitions - Géraldine Bois; Olivier Vanhée; Émilie Saunier (Contextes)
Publishers, writers and literary events’ organizers do not yet consider that readers’ blogs have the power to decisively influence book sales or literary values. However, these traditional actors of the literary world do tend to use blogs more and more frequently to promote books. They also acknowledge that some bloggers are great experts in assessing specific segments of the publishing world. Thus, in order to understand readers’ blogs, it is necessary not to locate them only within the « blogopshere ». The aim of this article is precisely to analyse how bloggers relate to the issues at stake in the literary world as a whole. Based on a thorough analysis of four very different blogs (interviews with the bloggers and content analysis of their blogs), this article unveils the skills of these « amateur » literary critics and assess their ambitions to play a role in the promotion and recognition of literary books.